Hannah Arendt e la determinazione dell’evento - Santoro, Valentina (B@belonline, 2020)
Without formalizing an event theory, Hannah Arendts structures her considerations over this topic, both historically and ontologically. From an ontological point of view the event is the discontinuity which introduces a new process possibility, originated by the faculty of action. This paper will introduce a theoretical investigation on Arendt’s concept of event, reflecting on three different determinations that characterize her theory of action: natality, miracle and foundation. The event as natality allows to totally rehabilitate the practical-political dimension of human beings in the theoretical matters, placing action as the foundation of existence. Natality manifests the uniqueness of human beings and constitutes the condition of possibility of the history. The event as miracle manifests human freedom as absolute spontaneity. The discussion of this aspect allows to analyze the Arendt’s concept of process according to nature and history. Moreover, the event as foundation allows to comprehend her conception of historical time as a ‘constellation of events’. Finally, the event as configuration of an absolute novelty that at the same time deeply affects the historical time, has a well-founded value, inaugurating and preserving a new political institution. Investigating the notion of event is the indispensable premise for understanding Arendt’s conception of history as the dimension of the possible.